2012
DOI: 10.1016/j.jacc.2012.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Common Variation in the NOS1AP Gene Is Associated With Drug-Induced QT Prolongation and Ventricular Arrhythmia

Abstract: BACKGROUND Use of anti-arrhythmic drugs is limited by the high incidence of serious adverse events including QT prolongation and torsades de pointes. Recent studies have demonstrated a role for NOS1AP gene variants in modulating QT interval in healthy subjects and modification of the severity of presentation and the risk of arrhythmias in LQTS. METHODS We carried out an association study using 167 SNPs spanning the NOS1AP gene in 58 Caucasian patients experiencing dLQTS and 87 Caucasian controls from the DAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 40 publications
(48 reference statements)
2
65
1
10
Order By: Relevance
“…In summary, we have shown that NOS1AP is a highly spliced protein, with the different isoforms having differential tissue expression and subcellular localizations and forming different signaling complexes. Given that NOS1AP has been implicated in a number of disorders, including bipolar disorder (23,37), schizophrenia (38), QT syndrome (14,39,40), anxiety (13), and post-C D…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we have shown that NOS1AP is a highly spliced protein, with the different isoforms having differential tissue expression and subcellular localizations and forming different signaling complexes. Given that NOS1AP has been implicated in a number of disorders, including bipolar disorder (23,37), schizophrenia (38), QT syndrome (14,39,40), anxiety (13), and post-C D…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that recent works have hypothesized that the response to antiarrhytmic drug therapy is influenced by a common polymorphism on chromosome 4q25 near PITX2 gene [37] and that the risk of proarrhythmic effect is modulated by common variants in nitric oxide synthase 1 adaptor protein [38], thus explaining the patient-to-patient variations in response and proarrhtmic effect.…”
Section: Drug Namementioning
confidence: 99%
“…44, 46 Common variants of NOS1AP have been reported to be associated with a significant increase in the risk of dLQTS. 47 Also, common variants in drug metabolism pathways may also predispose to dLQTS in a drug-specific fashion.…”
Section: Drugsmentioning
confidence: 99%